One-dimensional Schrödinger operators with general point interactions - Nizhnik, L. P.; Brasche, J. F. (Methods of Functional Analysis and Topology, 2013)
We consider various forms of boundary-value conditions for general one-dimensional Schrödinger operators with point interactions that include δ– and δ’– interactions, δ’– potential, and δ– magnetic potential. We give most simple spectral properties of such operators, and consider a possibility of finding their norm resolvent approximations.